IJCM_102A: Perception of Medical, Dental and Allied Health Science (AHS) Students towards Inter-professional Learning and Inter-professionalism in Mangalore - Chauhan Akshata J; Kumar Sunil; Singhal Abhinav; Khanuja Anushka; Karoshma MP; Kumar Nithin; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Interprofessional Education (IPE) has gained recognition in health professions education due to evolving healthcare roles and systems, emphasizing collaboration for quality care. Attitudinal barriers hinder its implementation, necessitating a deeper understanding of student perspectives. This study explores the attitudes of medical (MBBS), dental (BDS), and allied health science (AHS) students towards interprofessional learning (IPL) in a cross-sectional study at Kasturba Medical College (KMC) and Manipal College of Dental Sciences (MCODS), Manipal University, Mangalore. Methodology: A total of 205 students participated, comprising 150 MBBS, 40 BDS, and 15 AHS students. Data was collected through a modified semi-structured questionnaire, assessing attitudes towards IPL using Likert scales. Statistical analysis was conducted using SPSS ver. 20.0, with results expressed in medians and significance determined by the Mann-Whitney test. Results: Overall, students demonstrated positive attitudes towards IPL, with significant agreement that it enhances communication skills, facilitates professional relationships, and improves clinical problem-solving. Both MBBS and non-medical students expressed willingness to learn with peers from diverse healthcare disciplines, indicating a shared understanding of the importance of collaborative practice. Conclusion: The study highlights favourable attitudes among medical, dental, and allied health science students towards interprofessional learning, suggesting a readiness for collaboration in healthcare practice. These findings underscore the importance of incorporating interprofessional education opportunities within healthcare curricula to foster teamwork and enhance patient care outcomes.